Tafsir QS. Al-Hasyr Ayat 7 tentang Konsep HAM dan Distribusi Kekayaan di Tengah Krisis Ekonomi Global - Mely Bilqisti Aula (Comprehensive Journal of Islamic Studies, 2025)
Abstract This article discusses the relationship between the interpretation of QS. Al-Hasyr verse 7 with the concept of human rights (HAM) and the distribution of wealth in the context of the global economic crisis. Through a qualitative approach with library research methods and thematic analysis of the verses of the Qur'an, this study explores the values ​​of social justice, economic equality and protection of groups included in the Islamic economic system. QS. Al-Hasyr verse 7 contains the principle of fair distribution of wealth so that it is not only accumulated by the upper class, but is spread to various levels of society, including the poor. The interpretation of this verse shows how Islam not only guarantees individual rights, but also emphasizes socio-economic responsibility. The global economic crisis is often caused by violations of sharia principles such as usury and monopoly, so that Islamic economics with instruments such as zakat, infak, and sedekah is believed to be a solution to create equality and prosperity. This article shows that the integration of Islamic values ​​with the principles of human rights can provide a normative and practical framework in dealing with economic inequality in the era of globalization.